PERUBAHAN VIABILITAS DAN STRUKTUR SUBSELULER SPERMATOZOA DOMBA SETELAH PENGERINGBEKUAN - Saili, Takdir; Mudite Adnyana, I Ketut; Rachman Noor, Ronny; Agus Setiadi, Mohamad; Agungpriyono, Srihadi; Boediono, Arief (Jurnal Veteriner; Vol 10 No 4 (2009))
Several methods i.e. cooling, freezing, and freeze-drying have been widely used to preserve spermatozoa with various degree of success. Freeze-drying appears to provide a method to preserve spermatozoa in a dry state without requiring liquid nitrogen for storing frozen spermatozoa. Freeze-drying procedures can have a detrimental effect on plasma membrane and acrosomal cap of the spermatozoa. In this experiment study, the viability and subcellular changes of freeze-dried ram spermatozoa were evaluated using staining method and scanning electron microscopy. The results revealed that all freeze-dried spermatozoa were dead following evaluation using eosin staining and Hoechst-propidium iodide staining methods. Morover, plasma membrane and acrosomal cap of freeze-dried ram spermatozoa was disrupted observed using scanning electron microscope.
Keywords: freeze drying, ram spermatozoa, plasma membrane, acrosome cap